Effectiveness of first and second COVID‐19 mRNA vaccine monovalent booster doses during a period of circulation of Omicron variant sublineages: December 2021–July 2022. Issue 3 (1st March 2023) - Petrie, Joshua G.; King, Jennifer P.; McClure, David L.; Rolfes, Melissa A.; Meece, Jennifer K.; Pattinson, David; Neumann, Gabriele; Kawaoka, Yoshihiro; Belongia, Edward A.; McLean, Huong Q.
Abstract: Background: US recommendations for COVID‐19 vaccine boosters have expanded in terms of age groups covered and numbers of doses recommended, whereas evolution of Omicron sublineages raises questions about ongoing vaccine effectiveness. Methods: We estimated effectiveness of monovalent COVID‐19 mRNA booster vaccination versus two‐dose primary series during a period of Omicron variant virus circulation in a community cohort with active illness surveillance. Hazard ratios comparing SARS‐CoV‐2 infection between booster versus primary series vaccinated individuals were estimated using Cox proportional hazards models with time‐varying booster status. Models were adjusted for age and prior SARS‐CoV‐2 infection. The effectiveness of a second booster among adults ≥50 years of age was similarly estimated. Results: The analysis included 883 participants ranging in age, from 5 to >90 years. Relative effectiveness was 51% (95% CI: 34%, 64%) favoring the booster compared with primary series vaccination and did not vary by prior infection status. Relative effectiveness was 74% (95% CI: 57%, 84%) at 15 to 90 days after booster receipt, but declined to 42% (95% CI: 16%, 61%) after 91 to 180 days, and to 36% (95% CI: 3%, 58%) after 180 days. The relative effectiveness of a second booster compared to a single booster was 24% (95% CI: −40% to 61%). Conclusions: An mRNA vaccine booster dose added significant protection against SARS‐CoV‐2 infection, but protection decreased over time. A second booster did not add significant protection for adults ≥50 years of age. Uptake of recommended bivalent boosters should be encouraged to increase protection against Omicron BA.4/BA.5 sublineages.